Impact of sustained virological response to chronic hepatitic C antiviral therapy on new onset diabetes mellitus type 2 after controlling for metabolic syndrome. (23rd February 2017) - Pandya, Prashant; Pant, Chaitanya; Taylor, Ryan; Oni, Olurinde
Abstract : The high cost associated with antiviral treatment for chronic hepatitis C virus (HCV) infection mandates further investigation in the context of preventing complications such as type 2 diabetes mellitus (DM2). We determined the cumulative incidence of DM2 in subjects with chronic HCV infection who received concomitant pegylated interferon (Peg-IFN) and ribavirin. We conducted a retrospective analysis of data obtained from Veterans Administrations Informatics and Computing Infrastructure (VINCI) to identify an adult cohort of patients without diabetes with chronic HCV infection who received Peg-IFN-based therapy between October 2001 and December 2011. Patients with history of HIV, hepatitis B infection, hepatocellular cancer (HCC), non-HCC cancers, and history of transplantation were excluded. Sustained virological response (SVR) was defined as negative HCV RNA 3 months after completion of therapy. Using Cox proportional hazards regression for multivariable analysis, we determined that patients who achieved SVR were at a significantly less risk of developing DM2. Adjusted survival rates showed that the responders' group was significantly less likely to develop DM2 over time (HR 0.60, CI 0.48 to 0.74, p<0.001). Peg-IFN-based therapy in chronic HCV patients that resulted in SVR significantly decreased the risk of developing DM2 and independently predicts the development of new onset disease after controlling for correlates of metabolic syndrome.